Women and Death in Film, Television, and News - Dillman, Joanne Clarke. author. aut Link
XI, 207 p.
Keywords: Dead women litter the visual landscape of the 2000s. In this book, Clarke Dillman explains the contextual environment from which these images have arisen, how the images relate to (and sometimes contradict) the narratives they help to constitute, and the cultural work that dead women perform in visual texts.